Low-stress high-resilience organic silica gel and preparation method thereof

By adding specific nanofillers and modified nanosilicon dioxide to the silicone, the cross-linking network structure is optimized, and the elasticity reduction and permanent deformation of the silicone when repeatedly stressed is solved, achieving low stress and high rebound performance .

CN119463499AInactive Publication Date: 2025-02-18SUZHOU KESHIDA ELECTRONIC MATERIALS CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411540915.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When organic silicone is repeatedly subjected to stress, it is prone to decrease elasticity, cracks and permanent deformation, resulting in a decrease in the stability of the use system.

Method used

By using raw materials such as vinyl silicone oil, phenyl vinyl silicone oil and hydrogen-containing silicone oil, and adding vinyl silane coupling agent to modify nanofilters such as nanosilica, nanocarbon black, carbon nanotubes and graphene, the cross-linking is optimized. Network structure, reduce stress and improve resilience.

Benefits of technology

The low stress and high rebound properties of organic silicone are achieved, which reduces permanent deformation and improves the performance stability and service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005112769530000091
    Figure BDA0005112769530000091
Patent Text Reader

Abstract

The invention relates to the field of organic silica gel, and particularly discloses low-stress high-resilience organic silica gel and a preparation method thereof. The organic silica gel is prepared from the following raw materials in parts by weight: 75 to 80 parts of vinyl silicone oil, 10 to 15 parts of phenyl vinyl silicone oil, 35 to 40 parts of hydrogen-containing silicone oil, 0.1 to 0.5 part of a catalyst, 0.01 to 0.2 part of an inhibitor, 10 to 20 parts of vinyl silane coupling agent modified nano silicon dioxide, 3 to 5 parts of nano carbon black, 1 to 3 parts of carbon nanotubes and 3 to 5 parts of graphene. The material has high elasticity and small compression set.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of silicone, and more specifically, to a low-stress high-resilience organic silicone and a preparation method thereof. Background Art

[0002] Organic silica gel is a special rubber whose basic structural unit is silicon-oxygen chain link and side chain is connected with organic group. It combines the characteristics of organic and inorganic substances, and has good chemical inertness, biocompatibility, elasticity, electrical insulation, etc. Therefore, it is widely used as medical device materials, artificial organs, electronic packaging materials, seals and gaskets, food molds, etc. Organic silica gel is usually subjected to repeated stress during use. When silicone products are subjected to alternating stress, the structure and properties of the material change, resulting in permanent phase change, elasticity reduction, cracks and other problems, which reduce the stability of the use system. Organic silica gel, as a high-performance synthetic material, is widely used in production and life. Therefore, by analyzing the cross-linked network of organic silica gel, how to prepare a low-stress, high-rebound organic silica gel, improve the performance stability of organic silica gel products, reduce permanent deformation, and extend its service life is of great significance to production and life. Summary of the invention

[0003] In order to reduce the stress of organic silica gel and improve its rebound, the present application provides a low-stress high-rebound organic silica gel and a preparation method thereof.

[0004] In the first aspect, the present application provides a low-stress high-resilience organic silica gel, which adopts the following technical solution: A low-stress high-rebound organic silica gel comprises the following raw materials in parts by weight: 75-80 parts of vinyl silicone oil, 10-15 parts of phenyl vinyl silicone oil, 35-40 parts of hydrogen-containing silicone oil, 0.1-0.5 parts of catalyst, 0.01-0.2 parts of inhibitor, 10-20 parts of nano-silicon dioxide modified by vinyl silane coupling agent, 3-5 parts of nano-carbon black, 1-3 parts of carbon nanotubes and 3-5 parts of graphene.

[0005] By adopting the above technical scheme, a certain amount of vinyl silicone oil, phenyl vinyl silicone oil, and hydrogen silicone oil are used as the matrix. The silicone oils form certain crosslinks while the phenyl group provides certain steric hindrance, so that the molecular chain of the silicone oil can be extended within a certain limit after being stressed. By limiting the addition amount of phenyl vinyl silicone oil to a smaller amount, it will not cause difficulty in component orientation, and there will not be much residual stress after molding. The prepared silicone can achieve a certain elongation and is not easy to be permanently deformed; by adding a certain amount of nano carbon black and carbon nanotubes, the nano filler is better dispersed in the organic silicone matrix, providing support for the internal network gap of the cross-linked silicone. After the silicone is stressed, the force is transmitted and diffused, the structure is not easy to collapse, the compression permanent deformation is small, and the interface effect also produces more microcracks and elastic deformation, further enhancing the elastic performance. Graphene has a large specific surface area and stability. By adding a certain amount of graphene as a filler, the stability of the organic silicone rebound is improved. By adding a certain mass of vinyl silane coupling agent to modify the nano-silica, the dispersion of nano-silica in the silica gel matrix is ​​improved, providing a more stable support for the prepared silica gel. It can also participate in the cross-linking of silicone oil and further optimize the cross-linked network structure. When the organic silica gel receives alternating stress, the force can be better transmitted to the nano-silica with higher sphericity and converted into elastic deformation. The elastic performance of the prepared silica gel is better and it is not easy to form permanent deformation.

[0006] In a specific embodiment, the nano-silica modified by the vinyl silane coupling agent includes nano-silica modified by dimethoxydivinylsilane, nano-silica modified by diethoxydivinylsilane and nano-silica modified by dimethylphenylvinylsilane.

[0007] The applicant found that the organic silica gel obtained by limiting the vinyl silane coupling modified nano silica to include dimethoxydivinylsilane modified nano silica, diethoxydivinylsilane modified nano silica and dimethylphenylvinylsilane has better elasticity, lower internal stress and is less prone to permanent deformation. This may be because the modified nano silica, dimethoxydivinylsilane, dimethoxydivinylsilane and dimethylphenylvinylsilane have different strengths of electron-donating properties. After mixing with phenyl vinyl silicone oil with certain electron-withdrawing properties, a more uniform dispersion and arrangement is formed inside the organic silica gel. The stress can be evenly dispersed at the modified nano silica, and certain "quasi-crosslinking" points are formed with the silicone matrix. The prepared organic silica gel is more stable, the amount of hydrogen-containing silicone oil used is reduced, and the prepared organic silica gel has fewer crosslinking points whose activities are hindered, making the silicone gel more elastic and less prone to permanent deformation. At the same time, divinylsilane modified nano-silica and diethoxy divinylsilane modified nano-silica have two vinyl groups. The connection formed after the two vinyl groups participate in the cross-linking of silica gel is both stable and can move within a certain range. Dimethylphenyl vinyl silane has a phenyl group and a vinyl group. Through the steric hindrance of the phenyl group and the cross-linking of a vinyl group, a better connection is formed. By adding the above components together, a better cross-linking network is formed, and the distribution of cross-linking points inside the silica gel is more reasonable. The obtained organic silica gel has low stress and high resilience, and is not easy to deform permanently.

[0008] In a specific embodiment, the vinyl silicone oil includes a first vinyl silicone oil and a second vinyl silicone oil, and the viscosity of the first vinyl silicone oil is 20000-22000mm 2 / s, the viscosity of the second vinyl silicone oil is 10000-11000mm 2 / s.

[0009] By adopting the above scheme, the molecular weight of vinyl silicone oil is larger, the molecular chain of silicone oil is more flexible, and when subjected to external force, the chain movement can quickly change the conformation of the molecular chain, and the elasticity is better. The molecular chains can be entangled with each other to a certain extent, resulting in "quasi-crosslinking", which reduces the use of hydrogen-containing silicone oil. There are fewer crosslinking points where the movement inside the silicone is hindered, and the internal structure of the silicone can achieve better buffering after the alternating stress is applied. The silicone can be deformed but not easily deformed permanently. At the same time, there are fewer free ends inside the chain that cannot withstand stress and do not contribute to elasticity, which are not easily deformed permanently, and the performance of the prepared organic silicone is better.

[0010] In a specific embodiment, the vinyl content of the first vinyl silicone oil is 0.10±0.01 wt %, and the vinyl content of the second vinyl silicone oil is 0.12±0.01 wt %.

[0011] By adopting the above scheme, the vinyl content of the silicone oil is suitable for the components of the organic silica gel in this application, the formed cross-linked network structure is reasonable, and the elasticity of the prepared silica gel is better.

[0012] In a specific embodiment, the mass ratio of the dimethoxydivinylsilane modified nano-silica, diethoxydivinylsilane modified nano-silica and dimethylphenylvinylsilane modified nano-silica is: 1:1:(0.2-0.3).

[0013] By adopting the above scheme, at this mass ratio, its dispersion inside the organic silica gel is further optimized, the dimethylphenylvinylsilane is less, and the cross-linked network structure inside the prepared organic silica gel is better.

[0014] In a specific embodiment, the particle size of the nano-silica modified with the vinyl silane coupling agent is 100-120 nm.

[0015] By adopting the above scheme, nano silicon dioxide has high sphericity, large specific surface area, high reaction activity, can achieve better dispersion and modification, and the prepared organic silica gel is evenly dispersed after being subjected to force.

[0016] In a specific embodiment, the preparation steps of the vinyl silane coupling agent modified nano-silica include: adding nano-silica to an ethanol aqueous solution, stirring evenly to obtain a mixture, then adding a vinyl silane coupling agent to the mixture, stirring evenly, filtering, and drying to obtain vinyl silane modified nano-silica.

[0017] By adopting the above scheme, the preparation steps are relatively simple, the preparation effect is relatively stable, the prepared vinyl silane coupling agent modified nano-silica can be well dispersed and participate in the cross-linking inside the organic silica gel, and the prepared organic silica gel has good elasticity and resistance to permanent deformation.

[0018] In a specific embodiment, the catalyst comprises a platinum catalyst and the inhibitor comprises ethynyl cyclohexanol.

[0019] By adopting the above scheme, the catalytic effect is good, the cross-linking speed of the silica gel is appropriate, the structure is uniform and stable, and the elastic performance is good.

[0020] In a second aspect, the present application provides a method for preparing a low-stress high-resilience organic silica gel, comprising the following steps: S1: Weigh each component according to the mass ratio and stir evenly to obtain a mixture; S2: vacuum degassing the mixture of S1 at an absolute pressure of 0-22 KPa for 5-10 min to obtain a degassing material; S3: The defoaming material obtained in S2 is heated and cured to obtain organic silica gel.

[0021] By adopting the above technical solution, the preparation method is simple, the obtained polypropylene cast film has a uniform structure, each layer is tightly combined, and is relatively strong.

[0022] In a specific embodiment, the heat curing temperature is 90-110°C.

[0023] By adopting the above scheme, the cross-linking speed of the silicone is appropriate, the structure is uniform and stable, and the elasticity performance is good.

[0024] In summary, this application has the following beneficial effects: 1. The present application prepares organic silica gel by using a certain mass of vinyl silicone oil, phenyl vinyl silicone oil and hydrogen-containing silicone oil, and adding a certain mass of vinyl silane coupling agent modified nano-silica, and further limits the vinyl silane coupling agent modified nano-silica to include dimethoxydivinylsilane modified nano-silica, diethoxydivinylsilane modified nano-silica and dimethylphenylvinylsilane modified nano-silica and their mass ratio, thereby achieving uniform dispersion and support of nano-sized fillers, unhindered silica gel activity, and the prepared organic silica gel can better conduct and disperse after being subjected to alternating stress and transform into elastic deformation, with high elasticity and not easy to permanently deform.

[0025] 2. This application increases molecular chain entanglement, reduces the number of cross-linking points, and optimizes the cross-linking network structure by limiting the viscosity and vinyl content of vinyl silicone; further optimizes the elastic performance of silicone after being subjected to force by limiting the particle size of nano-silica; and further controls the structural stability by limiting the curing temperature. DETAILED DESCRIPTION

[0026] The following is a more specific description of the technical solution of the present invention in combination with several specific implementation examples. The embodiments are only partial embodiments of the present invention, not all of them. The following specific embodiments can be combined with each other, and the same or similar concepts or processes therein may not be repeated in some embodiments.

[0027] Unless otherwise specified, the experimental reagents in the preparation examples, embodiments and comparative examples are all conventional commercial brands or obtained through conventional preparation processes.

[0028] In the preparation examples, embodiments and comparative examples: phenyl vinyl silicone oil was purchased from Wuhan Lanabai Pharmaceutical Chemical DW3432; hydrogen-containing silicone oil CAS No.: 63148-57-2 was purchased from Nanjing Bermuda Biotechnology Co., Ltd.; the first vinyl silicone oil was purchased from Runhe Materials RH-Vi302, with a viscosity of 20000-22000mm2 / s and a vinyl content of 0.10±0.01wt%, the second vinyl silicone oil was purchased from Runhe Materials RH-Vi303, with a viscosity of 10000-11000mm2 / s and a vinyl content of 0.12±0.01wt%, and the third vinyl silicone oil was purchased from Runhe Materials RH-Vi304, with a viscosity of 5000-5500mm2 / s and a vinyl content of 0.16±0.01wt%; dimethoxydivinylsilane CAS No.: 129762-8 1-8 was purchased from Shaoyuan Technology Co., Ltd., diethoxydivinylsilane CAS No.: 67892-60-8 was purchased from Shengbang Silicone Technology Co., Ltd., dimethylphenylvinylsilane CAS No.: 1125-26-4 was purchased from Wengjiang Reagent PB25532; trivinylsilane CAS No.: 2372-31-8 was purchased from Jusheng JS4038; nano-silica was purchased from Zhejiang Manli Nano Technology Co., Ltd., the average particle size of 100nm is ML-SiO2-N100, and the average particle size of 300nm is ML-SiO2-N300; the catalyst is a platinum catalyst purchased from Dongguan Koxiwei Electronic Materials CGJ; the inhibitor is ethynyl cyclohexanol purchased from Hubei Hengjingrui Chemical Co., Ltd.; nano carbon black was purchased from Tianjin Yiborui Chemical Co., Ltd.; carbon nanotubes and graphene were purchased from Xianfeng Nano.

[0029] Preparation Example Preparation Example 1: Dimethoxydivinylsilane modified nanosilica 30 g of nano-silica was added to 1000 ml of 80% wt ethanol aqueous solution, and then 12 g of dimethoxydivinylsilane was added, stirred at 400 rpm for 1 hour, filtered, and dried at 80° C. to obtain dimethoxydivinylsilane-modified nano-silica.

[0030] The average particle size of the nano-silicon dioxide in this preparation example is 100 nm.

[0031] Preparation Example 2: Diethoxydivinylsilane modified nanosilica 30 g of nano-silica was added to 1000 ml of 80% wt ethanol aqueous solution, and then 12 g of diethoxydivinylsilane was added, stirred at 400 rpm for 1 hour, filtered, and dried at 80° C. to obtain diethoxydivinylsilane-modified nano-silica.

[0032] The average particle size of the nano-silicon dioxide in this preparation example is 100 nm.

[0033] Preparation Example 3: Dimethylphenylvinylsilane-modified nanosilica Add 30 g of nanosilica to 1000 ml of 80% wt ethanol aqueous solution, then add 12 g of dimethylphenylvinylsilane, stir at 400 rpm for 1 hour, filter, and dry at 80° C. to obtain dimethylphenylvinylsilane-modified nanosilica.

[0034] The average particle size of the nano-silicon dioxide in this preparation example is 100 nm.

[0035] Preparation Example 4: Dimethoxydivinylsilane modified nanosilica 30 g of nano-silica was added to 1000 ml of 80% wt ethanol aqueous solution, and then 12 g of dimethoxydivinylsilane was added, stirred at 400 rpm for 1 hour, filtered, and dried at 80° C. to obtain dimethoxydivinylsilane-modified nano-silica.

[0036] The average particle size of the nano-silicon dioxide in this preparation example is 300 nm.

[0037] Preparation Example 5: Trivinylsilane-modified nanosilica 30 g of nano-silica was added to 1000 ml of 80% wt ethanol aqueous solution, and then 12 g of trivinylsilane was added, stirred at 400 rpm for 1 hour, filtered, and dried at 80° C. to obtain trivinylsilane-modified nano-silica.

[0038] The average particle size of the nano-silicon dioxide in this preparation example is 100 nm.

[0039] Preparation Example 6: Epoxysilane-modified nano-silica 30 g of nano-silica was added to 1000 ml of 80% wt ethanol aqueous solution, and then 12 g of epoxysilane coupling agent KH-172 was added, stirred at 400 rpm for 1 hour, filtered, and dried at 80° C. to obtain epoxysilane-modified nano-silica.

[0040] The average particle size of the nano-silicon dioxide in this preparation example is 100 nm. Example

[0041] Example 1 In this embodiment, the organic silica gel includes the following components by mass: 750g of first vinyl silicone oil, 100g of phenyl vinyl silicone oil, 400g of hydrogenated silicone oil, 1g of catalyst, 0.1g of inhibitor, 100g of dimethoxydivinylsilane-modified nano-silica prepared in Preparation Example 1, 50g of nano-carbon black, 30g of carbon nanotubes, and 30g of graphene.

[0042] The preparation steps are as follows: S1: Weigh each component according to the mass ratio and stir evenly to obtain a mixture; S2: vacuum degassing the mixture of S1 at an absolute pressure of 10 KPa for 10 min to obtain a degassing material; S3: The defoaming material obtained in S2 is heated and cured at 100° C. to obtain organic silica gel.

[0043] Example 2 In this embodiment, the organic silica gel includes the following components in mass: 800 g of first vinyl silicone oil, 150 g of phenyl vinyl silicone oil, 350 g of hydrogenated silicone oil, 5 g of catalyst, 0.1 g of inhibitor, 120 g of dimethoxydivinylsilane-modified nano-silica prepared in Preparation Example 1, 50 g of nano-carbon black, 10 g of carbon nanotubes, and 50 g of graphene.

[0044] The preparation steps are as follows: S1: Weigh each component according to the mass ratio and stir evenly to obtain a mixture; S2: vacuum degassing the mixture of S1 at an absolute pressure of 10 KPa for 10 min to obtain a degassing material; S3: The defoaming material obtained in S2 is heated and cured at 100° C. to obtain organic silica gel.

[0045] Example 3 In this embodiment, the organic silica gel includes the following components in mass: 770g of first vinyl silicone oil, 120g of phenyl vinyl silicone oil, 400g of hydrogenated silicone oil, 1g of catalyst, 2g of inhibitor, 150g of dimethoxydivinylsilane-modified nano-silica prepared in Preparation Example 1, 50g of nano-carbon black, 30g of carbon nanotubes, and 50g of graphene.

[0046] The preparation steps are as follows: S1: Weigh each component according to the mass ratio and stir evenly to obtain a mixture; S2: vacuum degassing the mixture of S1 at an absolute pressure of 10 KPa for 10 min to obtain a degassing material; S3: The defoaming material obtained in S2 is heated and cured at 100° C. to obtain organic silica gel.

[0047] Example 4 In this embodiment, the organic silica gel includes the following components in mass: 400g of the first vinyl silicone oil, 350g of the second vinyl silicone oil, 100g of phenyl vinyl silicone oil, 400g of hydrogenated silicone oil, 1g of catalyst, 0.1g of inhibitor, 100g of dimethoxydivinylsilane-modified nano-silica prepared in Preparation Example 1, 50g of nano-carbon black, 30g of carbon nanotubes, and 30g of graphene.

[0048] The preparation steps are as follows: S1: Weigh each component according to the mass ratio and stir evenly to obtain a mixture; S2: vacuum degassing the mixture of S1 at an absolute pressure of 10 KPa for 10 min to obtain a degassing material; S3: The defoaming material obtained in S2 is heated and cured at 100° C. to obtain organic silica gel.

[0049] Example 5 In this embodiment, the organic silica gel includes the following components in mass: 750g of third vinyl silicone oil, 100g of phenyl vinyl silicone oil, 400g of hydrogenated silicone oil, 1g of catalyst, 0.1g of inhibitor, 100g of dimethoxydivinylsilane-modified nano-silica prepared in Preparation Example 1, 50g of nano-carbon black, 30g of carbon nanotubes, and 30g of graphene.

[0050] The preparation steps are as follows: S1: Weigh each component according to the mass ratio and stir evenly to obtain a mixture; S2: vacuum degassing the mixture of S1 at an absolute pressure of 10 KPa for 10 min to obtain a degassing material; S3: The defoaming material obtained in S2 is heated and cured at 100° C. to obtain organic silica gel.

[0051] Example 6 In this embodiment, the organic silica gel includes the following components in mass: 400g of the first vinyl silicone oil, 350g of the second vinyl silicone oil, 100g of phenyl vinyl silicone oil, 400g of hydrogen-containing silicone oil, 1g of a catalyst, 0.1g of an inhibitor, 40g of dimethoxydivinylsilane-modified nano-silica prepared in Preparation Example 1, 40g of diethoxydivinylsilane-modified nano-silica prepared in Preparation Example 2, 20g of dimethylphenylvinylsilane-modified nano-silica prepared in Preparation Example 3, 50g of nano carbon black, 30g of carbon nanotubes, and 30g of graphene.

[0052] The preparation steps are as follows: S1: Weigh each component according to the mass ratio and stir evenly to obtain a mixture; S2: vacuum degassing the mixture of S1 at an absolute pressure of 10 KPa for 10 min to obtain a degassing material; S3: The defoaming material obtained in S2 is heated and cured at 100° C. to obtain organic silica gel.

[0053] Example 7 In this embodiment, the organic silica gel includes the following components in mass: 400g of the first vinyl silicone oil, 350g of the second vinyl silicone oil, 100g of phenyl vinyl silicone oil, 400g of hydrogenated silicone oil, 1g of a catalyst, 0.1g of an inhibitor, 45g of dimethoxydivinylsilane-modified nano-silica prepared in Preparation Example 1, 45g of diethoxydivinylsilane-modified nano-silica prepared in Preparation Example 2, 10g of dimethylphenylvinylsilane-modified nano-silica prepared in Preparation Example 3, 50g of nano carbon black, 30g of carbon nanotubes, and 30g of graphene.

[0054] The preparation steps are as follows: S1: Weigh each component according to the mass ratio and stir evenly to obtain a mixture; S2: vacuum degassing the mixture of S1 at an absolute pressure of 10 KPa for 10 min to obtain a degassing material; S3: The defoaming material obtained in S2 is heated and cured at 100° C. to obtain organic silica gel.

[0055] Example 8 In this embodiment, the organic silica gel includes the following components in mass: 400g of the first vinyl silicone oil, 350g of the second vinyl silicone oil, 100g of phenyl vinyl silicone oil, 400g of hydrogenated silicone oil, 1g of a catalyst, 0.1g of an inhibitor, 45g of dimethoxydivinylsilane-modified nano-silica prepared in Preparation Example 4, 45g of diethoxydivinylsilane-modified nano-silica prepared in Preparation Example 2, 10g of dimethylphenylvinylsilane-modified nano-silica prepared in Preparation Example 3, 50g of nano carbon black, 30g of carbon nanotubes, and 30g of graphene.

[0056] The preparation steps are as follows: S1: Weigh each component according to the mass ratio and stir evenly to obtain a mixture; S2: vacuum degassing the mixture of S1 at an absolute pressure of 10 KPa for 10 min to obtain a degassing material; S3: The defoaming material obtained in S2 is heated and cured at 100° C. to obtain organic silica gel.

[0057] Example 9 In this embodiment, the organic silica gel includes the following components in mass: 400g of the first vinyl silicone oil, 350g of the second vinyl silicone oil, 100g of phenyl vinyl silicone oil, 400g of hydrogen-containing silicone oil, 1g of the catalyst, 0.1g of the inhibitor, 100g of trivinylsilane-modified nano-silica prepared in Preparation Example 5, 50g of nano-carbon black, 30g of carbon nanotubes, and 30g of graphene.

[0058] The preparation steps are as follows: S1: Weigh each component according to the mass ratio and stir evenly to obtain a mixture; S2: vacuum degassing the mixture of S1 at an absolute pressure of 10 KPa for 10 min to obtain a degassing material; S3: The defoaming material obtained in S2 is heated and cured at 100° C. to obtain organic silica gel.

[0059] Comparative Example Comparative Example 1 In this comparative example, the organic silica gel includes the following components by mass: 850g of the first vinyl silicone oil, 100g of phenyl vinyl silicone oil, 400g of hydrogenated silicone oil, 8g of catalyst, 0.1g of inhibitor, 50g of dimethoxydivinylsilane-modified nano-silica prepared in Preparation Example 1, 50g of nano-carbon black, 30g of carbon nanotubes, and 30g of graphene.

[0060] The preparation steps are as follows: S1: Weigh each component according to the mass ratio and stir evenly to obtain a mixture; S2: vacuum degassing the mixture of S1 at an absolute pressure of 10 KPa for 10 min to obtain a degassing material; S3: The defoaming material obtained in S2 is heated and cured at 100° C. to obtain organic silica gel.

[0061] Comparative Example 2 In this comparative example, the organic silica gel includes the following components by mass: 750g of the first vinyl silicone oil, 100g of phenyl vinyl silicone oil, 400g of hydrogen-containing silicone oil, 1g of a catalyst, 0.1g of an inhibitor, 100g of epoxysilane-modified nano-silica prepared in Preparation Example 6, 50g of nano-carbon black, 30g of carbon nanotubes, and 30g of graphene.

[0062] The preparation steps are as follows: S1: Weigh each component according to the mass ratio and stir evenly to obtain a mixture; S2: vacuum degassing the mixture of S1 at an absolute pressure of 10 KPa for 10 min to obtain a degassing material; S3: The defoaming material obtained in S2 is heated and cured at 100° C. to obtain organic silica gel.

[0063] Performance testing methods 1. Rebound performance According to GB / T1681-2009 Determination of the resilience of vulcanized rubber, the resilience of the organic silica gel in each embodiment and comparative example was tested. The test results are shown in Table 1.

[0064] 2. Compression set According to GB / T7759-2015 Determination of Compression Set of Vulcanized Rubber or Thermoplastic Rubber, the organic silica gel of each embodiment and comparative example was tested for compression set. The test results are shown in Table 1.

[0065] Table 1 In combination with Examples 1-3, Comparative Examples 1-2 and Table 1, the organic silica gel prepared in the present application has high elasticity and is not prone to permanent deformation.

[0066] In combination with Example 1, Examples 4-5 and Table 1, the present application adds two vinyl silicone oils of specific viscosities to form certain entanglements inside the prepared organic silica gel, so that stress can be buffered, permanent deformation is not easy, and elasticity is good.

[0067] In combination with Examples 1, 6-7, 9, Comparative Example 1 and Table 1, the present application adds vinyl silane coupling agent silane-modified nano-silica, especially dimethoxydivinylsilane-modified nano-silica, diethoxydivinylsilane-modified nano-silica and dimethylphenylvinylsilane-modified nano-silica, and limits them to a certain mass ratio, so that the internal cross-linking network of the prepared organic silica gel is evenly and reasonably distributed, with many movable "quasi-cross-linking" points, stable and highly elastic.

[0068] In combination with Examples 1, 7-8 and Table 1, the present application limits the particle size of nano-silicon dioxide to make it have both sphericity and reactivity, and the organic silica gel is more evenly dispersed after being subjected to force and is less likely to be permanently deformed.

[0069] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A low stress and high resilience organic silica gel, characterized in that: The invention comprises the following raw materials in parts by weight: 75-80 parts of vinyl silicone oil, 10-15 parts of phenyl vinyl silicone oil, 35-40 parts of hydrogen-containing silicone oil, 0.1-0.5 parts of catalyst, 0.01-0.2 parts of inhibitor, 10-20 parts of nano-silicon dioxide modified by vinyl silane coupling agent, 3-5 parts of nano-carbon black, 1-3 parts of carbon nanotubes and 3-5 parts of graphene.

2. The low stress and high resilience organic silica gel according to claim 1, characterized in that: The nano-silica modified by the vinyl silane coupling agent includes nano-silica modified by dimethoxydivinylsilane, nano-silica modified by diethoxydivinylsilane and nano-silica modified by dimethylphenylvinylsilane.

3. The low stress and high resilience organic silica gel according to claim 1, characterized in that: The vinyl silicone oil comprises a first vinyl silicone oil and a second vinyl silicone oil, wherein the viscosity of the first vinyl silicone oil is 20000-22000mm 2 / s, the viscosity of the second vinyl silicone oil is 10000-11000mm 2 / s.

4. The low stress and high resilience organic silica gel according to claim 1, characterized in that: The vinyl content of the first vinyl silicone oil is 0.10±0.01wt%, and the vinyl content of the second vinyl silicone oil is 0.12±0.01wt%.

5. The low stress and high resilience organic silica gel according to claim 2, characterized in that: The mass ratio of the dimethoxydivinylsilane modified nano-silica, the diethoxydivinylsilane modified nano-silica and the dimethylphenylvinylsilane modified nano-silica is 1:1:(0.2-0.3).

6. The low stress and high resilience organic silica gel according to claim 1, characterized in that: The particle size of the nano-silica modified by the vinyl silane coupling agent is 100-120nm.

7. The low stress and high resilience organic silica gel according to claim 1, characterized in that: The preparation steps of the silane coupling agent modified nano-silica include: adding nano-silica to ethanol aqueous solution, stirring evenly to obtain a mixture, then adding vinyl silane coupling agent to the mixture, stirring evenly, filtering, and drying to obtain vinyl silane modified nano-silica.

8. The low stress and high resilience organic silica gel according to claim 1, characterized in that: The catalyst comprises a platinum catalyst, and the inhibitor comprises ethynyl cyclohexanol.

9. The method for preparing the low-stress high-resilience organic silica gel according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1: Weigh each component according to the mass ratio and stir evenly to obtain a mixture; S2: vacuum degassing the mixture of S1 at an absolute pressure of 0-22 KPa for 5-10 min to obtain a degassing material; S3: The defoaming material obtained in S2 is heated and cured to obtain organic silica gel.

10. The method for preparing low-stress high-resilience organic silica gel according to claim 9, characterized in that: The heating curing temperature is 90-110°C.

Citation Information

Patent Citations

  • Modified nano silica for LED packaging material with high-refractivity and high mechanical strength, and preparation method of same

    CN103408798A

  • High-strength elastic invisible artificial skin

    CN108567997A

  • Black matrix composition, black matrix, and black matrix production method

    CN110036318A

  • Low-temperature molded liquid silicon rubber and preparation method thereof

    CN110423471A

  • Low-viscosity solvent-free organosilicon three-proofing adhesive and preparation method thereof

    CN115785898A